Neurocysticercosis : from diagnosis to treatment - Chavez, Mark A. (Neuroscience research progress, 2021)
"Neurocysticercosis, a preventable parasitic infection of the central nervous system caused by tapeworm, is a serious, potentially fatal disease that can cause neurologic syndromes such as epileptic seizures. Chapter One of this monograph describes the existing treatment options for neurocysticercosis, along with possible therapeutic alternatives under different drug development phases. Chapter Two explains the difficulties associated with correctly diagnosing neurocysticercosis, resulting from its varied clinical presentation, and mentions current guidelines of diagnostic criteria for neurocysticercosis. Chapter Three describes the various merits and demerits of techniques for detecting the parasites associated with neurocysticercosis, which include radioimaging, genotyping of cysts, and antibody, antigen, and nucleic acid detection in body fluids"--